1999
DOI: 10.1192/bjp.175.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, context and consequences of memory recovery among adults in therapy

Abstract: Some of the data are consistent with memories being of iatrogenic origin, but other data clearly point to the need for additional explanations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 17 publications
5
25
2
Order By: Relevance
“…Nevertheless, it is of great concern that, unlike the great majority of qualified clinical psychologists, some alternative therapists continue to endorse mistaken ideas, for example, that people's conscious memories can go back to birth and that hypnotically retrieved memories are reliable (Andrews et al, 1999; Brewin & Andrews, 2014). These beliefs may foster the inappropriate practices we and others have identified.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is of great concern that, unlike the great majority of qualified clinical psychologists, some alternative therapists continue to endorse mistaken ideas, for example, that people's conscious memories can go back to birth and that hypnotically retrieved memories are reliable (Andrews et al, 1999; Brewin & Andrews, 2014). These beliefs may foster the inappropriate practices we and others have identified.…”
Section: Discussionmentioning
confidence: 99%
“…Memory recovery therapists believe that certain psychological symptoms are indicative of a history of childhood maltreatment. As such, according to survey data, therapists inside and outside of the United States engage in memory recovery procedures such as hypnosis, use of imagery/imagination, dream interpretation, age regression including hypnotic age regression, bibliotherapy, and symptom interpretation (Andrews et al, 1999;Ost, Wright, Easton, Hope, & French, 2013;Poole, Lindsay, Memon, & Bull, 1995;Yapko, 1994;see Lynn et al, 2015, for a review). Implementation of the aforementioned techniques is often accompanied by therapist suggestion that maltreatment occurred along with verbal statements that create expectancies denoting that recovering specific instances of maltreatment is plausible.…”
Section: Introductionmentioning
confidence: 99%
“…They are, however, consistent with the accounts of therapists reporting on their patients. In our work (Andrews et al, 1999(Andrews et al, , 2000, detailed interviews with practising psychologists concerning 236 patients with recovered memory revealed that in 69% of cases recovery was from prior total amnesia. In the remaining 31% degree of prior knowledge varied from a vague sense or suspicion to partial familiarity with the events.…”
Section: In This Article Mcnallymentioning
confidence: 92%